2023
DOI: 10.1002/ptr.7965
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid metabolism disorders and potential therapeutic traditional Chinese medicines in cardiovascular diseases

Abstract: Cardiovascular diseases are currently the primary cause of mortality in the whole world. Growing evidence indicated that the disturbances in cardiac fatty acid metabolism are crucial contributors in the development of cardiovascular diseases. The abnormal cardiac fatty acid metabolism usually leads to energy deficit, oxidative stress, excessive apoptosis, and inflammation. Targeting fatty acid metabolism has been regarded as a novel approach to the treatment of cardiovascular diseases. However, there are curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 197 publications
(229 reference statements)
0
0
0
Order By: Relevance
“…With the improvement of people's living standard, cardiovascular disease has become a kind of disease threatening human health [1]. Studies have shown that the current incidence and mortality of cardiovascular diseases have exceeded malignant tumors, becoming the first incidence of disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of people's living standard, cardiovascular disease has become a kind of disease threatening human health [1]. Studies have shown that the current incidence and mortality of cardiovascular diseases have exceeded malignant tumors, becoming the first incidence of disease [2].…”
Section: Introductionmentioning
confidence: 99%